Monetary policies and economic management: Evidence from Sub-Saharan Africa - Nwosu, Kanayo Chike; Okafor, Ekwunife Gabriel; Egbunike, Chinedu F. (Journal of Governance and Accountability Studies, 2023)
Purpose: The objective of this paper is to empirically analyze the application of monetary policies for economic management in Sub-Saharan African countries. The study used time series data from two African countries, specifically Kenya and Rwanda to examine the effect of broad money on the Gross Domestic Product growth rate. Research methodology: The study relied on secondary data; obtained from the World Bank Development Indicators database. The study analyzed the data using both descriptive and inferential statistical techniques. The hypothesis was tested using the Ordinary Least Squares (OLS) technique. The data were checked for normality and subjected to Unit Root tests using the Dickey-Fuller, Augmented Dickey-Fuller and Phillips-Perron text prior to further analysis. Results: The results confirmed the stationarity of the data. The descriptive statistics showed that all variables were normally distributed. The OLS result showed that broad money growth had a positive statistically significant effect on the GDP growth rate of both countries. Limitations: The study focused on two sub-Saharan African countries. Contribution: This study explicates the fact that in order to have a robust financial system, which eventually results in sustainable economic development, solid monetary policies must be maintained. Practical Implication: The implication of this study is the identification of how responsible, long-term fiscal and budgetary stance encourages economic growth. Novelty: The study focuses on the application of monetary policies in the economic management of Sub-Saharan African countries; with a particular emphasis on Kenya and Rwanda. These two countries have recorded remarkable growth in Sub-Saharan Africa compared to other countries.